Genotypic Variability of Total Phenolic Compounds and Antioxidant Activity in Jerusalem Artichoke (Helianthus tuberosus L.) Germplasm - Ruttanaprasert, Ruttanachira; Jogloy, Sanun; Sennoi, Rattikarn; Aninbon, Chorkaew; Puttha, Ratchanee; Janket, Anon; Pinta, Wanwipa; Senawong, Thanaset (AGRIVITA Journal of Agricultural Science, 2024)
This research examines the variability in tuber yield, yield component, phenolic compounds, and antioxidant activity of twenty-five Jerusalem artichoke genotypes. The field experiment is arranged using a randomized complete block design with three replications. The plant tubers are harvested at maturity and recorded for tuber dry weight, total phenolic content, and antioxidant activity. The results show significant genetic variations in tuber dry weight, phenolic content, and antioxidant activity determined by FRAP and ABTS methods. Significant and positive correlations are found among individual tuber dry weight, number of tubers per plant, tuber dry weight, including phenolic content, and antioxidant activity determined by the FRAP method. Jerusalem artichoke genotypes are classified into five groups based on tuber dry weight, phenolic content, and antioxidant activity determined by DPPH and FRAP methods. KT504 is identified as the accession with high levels of tuber dry weight, phenolic content, and antioxidant activity, and this genotype might be used as a material source for the pharmaceutical industry. Total phenolic content in the tuber can serve as an index for selecting Jerusalem artichoke genotypes with direct high antioxidant activity.